THE EFFECT OF FINANCIAL LEVERAGE ON DEBT REPAYMENT CAPACITY : EVIDENCE FROM LISTED SHIPPING COMPANY IN INDONESIA - Danu Ade Setiawan (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2018)
Contrast with its potentiality in the largest Archipelago country on the world, shipping industry in Indonesia show unsatisfactory condition whereas its industry’s national growth is below the overall industries growth and industry’s non-performing loan (NPL) rate is higher than national NPL. This condition is caused by the nature of the shipping industry with a high level of business uncertainty and their liability’s structure are dominated by banks and other financial institutions’ long-term debts. This research examines the relationship between financial leverage variable on the debt repayment capacity variable specifically to the banks and other financial institutions. The research population is shipping companies listed in Indonesia stock exchange with a number of samples is 12 companies. The consolidated financial statements in the period between 2014 and 2015 from the selected sample are used in this research. Based on literature review, the variable of company’s leverage is represented by a debt-equity ratio (DER). On the debt repayment capacity variable, the qualitative research method that is Delphi method is applied to define the ratio represented the variable. As the result, the debt repayment capacity variable is represented by Debt Security Coverage Ratio (DSCR). The statistical method that is used in this research is correlation analysis. Correlation analysis is a group of techniques to measure the relationship between two variables that are financial leverage represented by DER and debt repayment capacity represented by DSCR. The result shows that there is a negative correlation between financial leverage that is represented by DER and debt repayment capacity that is represented by DSCR. However, the correlation between them is considered weak with Pearson correlation coefficient less than 0,5 in absolute value or the influence of DER to the DSCR is insignificant.